2018
DOI: 10.1038/s41598-017-18761-5
|View full text |Cite
|
Sign up to set email alerts
|

Increased heart rate after exercise facilitates the processing of fearful but not disgusted faces

Abstract: Embodied theories of emotion assume that emotional processing is grounded in bodily and affective processes. Accordingly, the perception of an emotion re-enacts congruent sensory and affective states; and conversely, bodily states congruent with a specific emotion facilitate emotional processing. This study tests whether the ability to process facial expressions (faces having a neutral expression, expressing fear, or disgust) can be influenced by making the participants’ body state congruent with the expressed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
35
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 43 publications
(44 citation statements)
references
References 102 publications
(93 reference statements)
8
35
0
1
Order By: Relevance
“…A previous study that manipulated participants' physiological feedback during exercise reported that emotional intensity and salience of neutral faces was enhanced by false feedback of increased HR (50). Other studies have reported that providing feedback on HR influences the perceived attractiveness of stimuli (51), and that increasing HR by exercise sensitizes to fearful stimuli (52). Our present study and the aforementioned studies show that providing false physiological feedback is an effective method for probing interoceptive processing and producing interoceptive illusions.…”
Section: Discussionsupporting
confidence: 68%
“…A previous study that manipulated participants' physiological feedback during exercise reported that emotional intensity and salience of neutral faces was enhanced by false feedback of increased HR (50). Other studies have reported that providing feedback on HR influences the perceived attractiveness of stimuli (51), and that increasing HR by exercise sensitizes to fearful stimuli (52). Our present study and the aforementioned studies show that providing false physiological feedback is an effective method for probing interoceptive processing and producing interoceptive illusions.…”
Section: Discussionsupporting
confidence: 68%
“…In a second step, a mean vector of all participants was computed via vector addition of individual means divided by their number, showing the average self-paced picture onset in the cardiac cycle across the group, and weighted by its length (mean resultant length ϱ) to reflect the spread of individual means around the circle. As a measure of concentration of circular data, ϱ was integrated in a subsequent Rayleigh test for uniformity (Pewsey, Neuhäuser, & Ruxton, 2013): if ϱ gets sufficiently high to exceed a threshold value (i.e., the set of individual means is not spread evenly across the cardiac cycle), the data can be interpreted as too locally clustered to be consistent with a uniform distribution that served as null hypothesis (Pewsey et al, 2013). The code for individual and group-level circular analysis can be found on GitHub (https://github.com/SKunzendorf/0303_INCASI).…”
Section: Circular Analysismentioning
confidence: 99%
“…Evidence for the influential role the body's physiological condition has on emotional, perceptual processing was found in a study that manipulated (increased) heart rate before participants performed a gender-categorization task with (male and female) faces expressing an emotion congruent with the interoception of an increased heart rate (fear), an incongruent emotion (disgust), or neutrality (Pezzulo et al, 2018). Participants performed the task in two conditions: in a rest condition, when they had remained at rest to maintain their baseline heart rate; and in an exercise condition, when they had performed physical exercise to build and sustain an increased heart rate.…”
Section: Introductionmentioning
confidence: 99%